Is Self-employment a Way to Escape from Skill Mismatches? - Judit Albiol Sanchez; Luis Diaz-Serrano; Graciela Teruel (Institute for the Study of Labor (IZA), 2015)
During the last two decades, skill mismatches have become one of the most important issues of policy concern in the EU (European Commission, 2008). Hence, the literature has stressed the necessity to reduce skill mismatches. We contribute to this literature by analyzing the impact of the transition from salaried employment to self-employment on self-reported skill mismatches. To do so, we resort to the European Community Household Panel (ECHP) covering the period 1994-2001. Using panel data, we track individuals over time and measure their self-reported skill mismatch before and after the transition. Our empirical findings indicate not only that the average self-employee is less likely to declare being skill-mismatched but also that those individuals who transit from salaried employment to self-employment reduce their probability of skill mismatches after the transition.
Keywords: L26; J24; B23; 330; self-employment; skill mismatches; salaried employment